An insight of early PrP‐E200K aggregation by combined molecular dynamics/fragment molecular orbital approaches. Issue 1 (16th November 2018) - Paciotti, Roberto; Storchi, Loriano; Marrone, Alessandro
Abstract: Unveiling the events leading to the formation of prion particles is a nowadays challenge in the field of neurochemistry. Pathogenic mutants of prion protein (PrP) are characterized by both an intrinsic tendency to aggregation and scrapie conversion propensity. However, the question about a possible correlation between these two events lasts still unanswered. Here, a multilayered computational workflow was employed to investigate structure, stability, and molecular interaction properties of a dimer of PrP C ‐E200K, a well‐known mutant of the PrP that represents a reduced model of early aggregates of this protein. Based on the combination of molecular dynamics and quantum mechanical approaches, this study provided for an in depth insight of PrP C ‐E200K dimer in terms of residue‐residue interactions. Assembly hypotheses for the early aggregation of PrP C ‐E200K are paved and compared with PrP Sc models reported in the literature to find a structural link between early and late (scrapie) aggregates of this protein.